The Effectiveness of Acupressure Pen and Active Stretching (Acupenas) on Fasting Blood Sugar Levels among Type 2 Diabetes Mellitus Patient - Iche Nila Kusna; Sudirman Sudirman; Budi Widiyanto; Supriyana Supriyana; Ta'adi Ta'adi (International Journal of Nursing and Health Services (IJNHS), 2020)
International Diabetes Federation (IDF) reported that the number of DM patients worldwide increases every year. Indonesia ranks sixth with the highest DM prevalence globally after China, India, the United States, Brazil, and Mexico. The main problem caused by DM patients is the instability of blood sugar levels. Alternative treatments for Diabetes Mellitus with complementary therapy are acupressure therapy, which can prevent complications and improve blood sugar levels. This study examines the effectiveness of acupressure pen and active stretching on fasting blood sugar levels in type 2 diabetes mellitus patients. This true research experiment with the design using pre-test and post-test control group design. Data collection involved 38 respondents of type 2 Diabetes Mellitus patients, selected through technique probability sampling with simple random sampling. The intervention group was received the acupressure pen and active stretching (Acupenas) therapy with metformin drug 2x500 mg. In contrast, the control group only received therapy metformin drug 2x500 mg without acupressure pen and active stretching. Independent t-test results showed significant differences with the average fasting blood sugar levels p-value 0.002 (<0.05). It was indicated that the intervention group is better at lowering blood sugar levels than the control group seen from the higher difference value. Complementary therapy is acupressure pen and active stretching was effective in reducing blood sugar levels in type 2 Diabetes Mellitus patients.